Analisis Penanganan Kasus Narkoba Ditinjau Dari Perspektif Hukum dan Masyarakat - Amanda, Niken Dwi; Nurdin, Merry Kurniawati; Darmawan, Cinta Rizqareka; Az Zahra, Hilyah; Mawaddah, Ananda Ratu; Nugraha, Setyo; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The problem of drug abuse is a serious challenge in many countries, including Indonesia. The government has adopted a comprehensive approach to address it, through law enforcement and prevention. Handling drug cases involves legal aspects such as policies, regulations, and legal processes, as well as societal views that influence approaches to treatment and rehabilitation. Therefore, analysis from both legal and societal perspectives is important to understand the effectiveness of drug treatment and find better solutions. The purpose of this study is to provide a thorough understanding of the handling of drug cases from two perspectives, law and society, and analyze its effectiveness. In this research the author uses a normative method with a statutory approach. The results show that much still needs to be done to improve the effectiveness and fairness in handling drug cases in Indonesia. Community involvement and open dialogue between legal institutions and the community are essential to build public trust and ensure effective legal policies. Thus, it is important to ensure a transparent and fair judicial process. Continuous efforts need to be made to improve transparency, independence and fairness in the judicial process. Involving the public in decision-making processes and open dialog is also important to build trust and ensure effective legal policies